Sonoelastography in Orthopaedics: Fact or Fashion?. Issue 2 (28th February 2017) - Kuyucu, Ersin; Erdil, Mehmet; Koçyiğit, Figen; Kocabey, Yavuz
Tissues are exposed to various forces. They change in shape and deform as a result of these forces. The tendency of the tissue to deform when opposing forces are applied is defined as elastic modulus. Different tissues have different elastic modulus. Elastic modulus also changes in time because of changes in tissue components in response to inflammation, injury and degeneration. Evaluation of elasticity of tissues by ultrasonography has started in the 1990s and gained popularity in time. 83 patients (51 female, 32 male) with different muscıuloskeletal diseases (34 lateral epicondylitis, 20 plantar fasciitis, 25 shoulder impingement syndrome, four gastrocnemius sprain) were evaluated by sonoelastography (Logiq E9; GE Healthcare, Milwaukee, WI, USA) both for diagnosis and treatment follow-up. Sonoelastographic evaluations were performed by the same radiologist (AK) who was experienced in ultrasonography. Color scaling and strain ratio were used for analysis of sonoelastography images. Three orthopedists (YK, ME, EK) evaluated the patients. Appropriate conservative treatment was recommended for management in all of the patients. The sonoelastographic findings of the involved extremity were significantly different from the health side in all patients. Sonoelastography can evaluate dynamic properties of tissues. Orthopedics is interested in different tissues like cartilage, muscle, and bone. Therefore, the use of sonoelastography in orthopaedic science seems to increase. Availability, repeatability, and low financial cost are the other important advantages of sonoelastography in clinical practice. Figure-1 Thickness of right (a) and left plantar fascia (b) (arrow). Despite left plantar fascia being thicker, both of them are in the standard range.(USG) Figure-2 (Sonoelastography revealed mostly blue and green pattern on the right plantar enthesis (arrow) with low strain index (0.1) (a).Sonoelastography revealed green, yellow, and red pattern on the left plantar enthesis (arrow) with high strain index (0.4) (b).